Barrier of early initiation of breastfeeding among postnatal mothers - Shakya, Nona; Shakya, Mana Maya (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Early initiation of breastfeeding within one hour of birth decreases infant morbidity and mortality, and it helps promote exclusive breastfeeding. Despite the benefits of early initiation of breastfeeding, the practice is far from adequate. We aim to identify the barriers to the early initiation of breastfeeding among postnatal mothers. Method: A cross-sectional analytical study was carried out among the postnatal ward of Manipal Teaching Hospital from 1 June to 30 August 2017. Consecutive sampling was used. Ethical permission was obtained. Data was collected through face-to-face interviews using a semi-structured questionnaire, including demographics of mother and infant, and time of initiation of feeding. SPSS was used for descriptive analysis of demographics, and the association of factors for the initiation of early breastfeeding was analyzed to draw the inference. Result: Out of 244 postnatal mothers, the early initiation of breastfeeding was done by 19.7%, and 82.4% provided prelacteal feeds of infant formula. Delayed breastfeeding was associated with caesarean section (OR: 21.99; 95% CI 5.55-87.03), prelacteal feeding (OR: 7.49; 95% CI 2.72-20.66), and lack of antenatal checkup visit (OR: 7.38; 95% CI 2.3-23.73). Conclusion: Early initiation of breastfeeding was low (19.7%) in postnatal mothers, with barriers to breastfeeding identified as caesarean delivery, prelacteal feeding, lack of antenatal checkup visits.